2015
DOI: 10.1007/s12262-015-1264-1
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Propiverine Hydrochloride for Overactive Bladder in Adult: a Systematic Review and Meta-analysis

Abstract: We carried out a systematic review and metaanalysis to assess the efficacy and safety of propiverine for treating overactive bladder (OAB) in adult. A literature review was performed to identify all published randomized placebocontrolled trials (RCT) of propiverine for the treatment of OAB. The search included the following databases: PUBMED and EMBASE. The reference lists of retrieved studies were also investigated. A systematic review and meta-analysis were conducted. Ten publications involving nine differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 19 publications
0
7
0
2
Order By: Relevance
“…According to the results of five studies involving 2891 participants (1648 in the treatment group and 1243 in the control group) on the effects of propiverine hydrochloride on the overactive bladder, the increase in urine volume per voiding (ml) was significantly higher in the propiverine group compared to the control group (P< 0.00001) (Figure 1). 11 In dose determination studies, it has been reported that 50% improvement was observed in the efficacy parameters in the group given 15 mg/day, while the efficacy reached 80% in the group given 30 mg/day. 21 The subjective improvement in OAB patients with the use of propiverine has been shown to be 77%.…”
Section: Overview Of Literaturementioning
confidence: 99%
“…According to the results of five studies involving 2891 participants (1648 in the treatment group and 1243 in the control group) on the effects of propiverine hydrochloride on the overactive bladder, the increase in urine volume per voiding (ml) was significantly higher in the propiverine group compared to the control group (P< 0.00001) (Figure 1). 11 In dose determination studies, it has been reported that 50% improvement was observed in the efficacy parameters in the group given 15 mg/day, while the efficacy reached 80% in the group given 30 mg/day. 21 The subjective improvement in OAB patients with the use of propiverine has been shown to be 77%.…”
Section: Overview Of Literaturementioning
confidence: 99%
“…Perbandingan Efektivitas Imidafenacin dengan Golongan Antimuskarinik Lain (Huang, et al, 2015;Wu, et al, 2020) Tabel 3. Perbandingan Keamanan Imidafenacin dengan Golongan Antimuskarinik Lain (Huang et al, 2015;Wu et al, 2020) Pengarang Hasil kajian sistematik dan meta-analisis terkait perbedaan efektivitas imida-fenacin dengan golongan antimuskarinik lain pada tabel 2, dan kajian terkait keamanan pada tabel 3 terlihat mayoritas penelitian menunjukkan efektivitas imidafenacin yang setara dibandingkan dengan antimuskarinik yang lain. Dengan kata lain, penggunaan imidafenacin tidak menghasilkan efek positif terhadap pasien yang lebih superior dibandingkan dengan pembanding termasuk tolterodine, fesoterodine, propiverine, dan solifenacin.…”
Section: Efektivitas Dan Keamanan Imidafenacinunclassified
“…Dengan kata lain, penggunaan imidafenacin tidak menghasilkan efek positif terhadap pasien yang lebih superior dibandingkan dengan pembanding termasuk tolterodine, fesoterodine, propiverine, dan solifenacin. Ditinjau dari sisi keamanan penggunaan, imidafenacin lebih jarang menyebabkan ROTD berupa mulut kering (relative risk [RR] 0,87; 95% confidence interval [CI] 0,75-1,00) dan konstipasi (RR 0,68; 95% CI 0,50-0,93) bila dibandingkan dengan golongan anti-muskarinik lainnya (Huang, et al, 2015;Nazir, et al, 2018;Wu, et al, 2020). Namun demikian, kejadian jenis ROTD yang lain relatif tidak berbeda secara signifikan antara kelompok yang mendapat imidafenacin dan antimiskarinik lain yang ada di Indonesia.…”
Section: Efektivitas Dan Keamanan Imidafenacinunclassified
“…Propiverine has both an antimuscarinic action and also acts as an inhibitor of cellular calcium influx, thereby reducing muscle spasm. 25 It has been shown to suppress adenosine triphosphate (ATP)-induced overactivity in rats, and may therefore also have an effect on sensory pathways. 26 It has been shown to be more effective than placebo in a meta-analysis, although sample sizes were not large and unpublished data were not included in the analysis, which could have resulted in bias.…”
Section: Antimuscarinicsmentioning
confidence: 99%
“…26 It has been shown to be more effective than placebo in a meta-analysis, although sample sizes were not large and unpublished data were not included in the analysis, which could have resulted in bias. 25 It is available in both IR and ER formulations, at a dose of 15 mg one to three times daily as IR and 30 mg once daily as ER. 13…”
Section: Antimuscarinicsmentioning
confidence: 99%